2019
DOI: 10.1101/705061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct neural markers for intentional and unintentional task unrelated thought

Abstract: Studies suggest that generating thought unrelated to the task in hand is accompanied by a reduction of attention to external task-relevant information. This observations led contemporary theory to suggest multiple component processes contribute to patterns of ongoing thought. The present study used EEG to seek support for these component-process accounts by examining the neural correlates of deliberate and spontaneous task unrelated thought. EEG activity was compared prior to reports of ongoing thought during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 122 publications
(152 reference statements)
6
33
2
Order By: Relevance
“…Evidence for this view comes from studies showing that different facets of the off-task experience are a function of both shared and distinct neurocognitive profiles. For example, a recent study by the authors of the present paper (Martel et al, 2019) shows that one of the features of off-task thought, the degree of intentionality, can be understood as the interplay between bottom-up and top-down features of attention. More specifically, of the two processes that are assumed by contemporary accounts to be critical during off-task mental activity (Smallwood, 2013a), perceptual decoupling and executive control, the latter is thought to contribute exclusively to off-task thought when engaged in a deliberate manner.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…Evidence for this view comes from studies showing that different facets of the off-task experience are a function of both shared and distinct neurocognitive profiles. For example, a recent study by the authors of the present paper (Martel et al, 2019) shows that one of the features of off-task thought, the degree of intentionality, can be understood as the interplay between bottom-up and top-down features of attention. More specifically, of the two processes that are assumed by contemporary accounts to be critical during off-task mental activity (Smallwood, 2013a), perceptual decoupling and executive control, the latter is thought to contribute exclusively to off-task thought when engaged in a deliberate manner.…”
Section: Introductionmentioning
confidence: 73%
“…Although the role of perceptual decoupling is now well understood, the role of executive control in off-task states remains more elusive and a central question of the literature McVay & Kane, 2010;Smallwood, 2013b;Smallwood & Schooler, 2006;Watkins, 2008), with evidence for its involvement in both off-task and task-related thought. The recent study led by the authors of the current work (Martel et al, 2019) investigating the intentionality dimension of off-task experiences found that spontaneous and deliberate forms of off-task states differ on several EEG features. Among these markers, alpha synchronisation, associated with perceptual inhibition (Foxe & Snyder, 2011) and internal attention (Benedek, Schickel, Jauk, Fink, & Neubauer, 2014;Cooper, Croft, Dominey, Burgess, & Gruzelier, 2003;Katahira et al, 2018), was found to be the most prominent marker of deliberate off-task states and interpreted as reflecting top down inhibition of irrelevant sensory input.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations